The Influence Of Education, Training, And Service Quality On The Performance Of Employees At The Kupang Search And Rescue Office (SAR) - Lamawuran, Wilen Wadan Penana; Yasinto, Yulius; Man, Stanis (SEAN Institute, 2024)
The Employee of Search and Research (SAR) Kupang Office have not accomplished the best performance. This indicated that those employees are need more training and educationto achieved their full performance. The purpose of this study was to see the role of education, training, and service quality in shaping employee performance at the Kupang Search and Rescue Office (SAR). This study used a quantitative method, with a data collection instrument in the form of a questionnaire. The data collected were then analyzed using SPSS to see the results of multiple linear regression. The results of the study showed that partially and simultaneously, education, training, and service quality had a positive and significant effect on employee performance at the Kupang Search and Rescue Office (SAR)